2014
DOI: 10.1002/anie.201409293
|View full text |Cite
|
Sign up to set email alerts
|

Ring‐Opening Polymerization of Prodrugs: A Versatile Approach to Prepare Well‐Defined Drug‐Loaded Nanoparticles

Abstract: We report a new methodology for the synthesis of polymer-drug conjugates from “compound”—all in one—prodrug monomers that consist of a cyclic polymerizable group that is appended to a drug through a cleavable linker. We show that organocatalyzed ring-opening polymerization can polymerize these monomers into well-defined polymer prodrugs that are designed to self-assemble into nanoparticles and release drug in response to a physiologically relevant stimulus. This method is compatible with structurally diverse d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(80 citation statements)
references
References 44 publications
(32 reference statements)
1
79
0
Order By: Relevance
“…As compared to polymer–drug conjugates, physically loaded drug formulations are usually less stable and more prone to premature drug release that would largely reduce their tumor targetability . Polymer–drug conjugates are, however, often perplexed by their multistep synthesis and/or inefficient activation at the site of action …”
Section: Introductionmentioning
confidence: 99%
“…As compared to polymer–drug conjugates, physically loaded drug formulations are usually less stable and more prone to premature drug release that would largely reduce their tumor targetability . Polymer–drug conjugates are, however, often perplexed by their multistep synthesis and/or inefficient activation at the site of action …”
Section: Introductionmentioning
confidence: 99%
“…In order to synthesize nanocarriers of GEM based on a biodegradable, dendritic polymer, we used hyperbranched PG‐ co ‐PCL as the macroinitiator core. To include a drug‐bearing domain along with a release trigger, we first grafted a pentafluorophenyl ester appended polycarbonate from PG‐ co ‐PCL to yield compound 3 , using cyclic carbonate as the monomer and 1,8‐diazabicyclo [5.4.0] undec‐7‐ene (DBU) as the catalyst . The hyperbranched PG‐ co ‐PCL macroinitiator provided multiple reaction sites from which the polycarbonate (PC) block was generated.…”
Section: Resultsmentioning
confidence: 99%
“…We have also investigated the potential of using PG‐ co ‐PCL to non‐covalently stabilize GEM, taking the advantage of the strong hydrogen bond–forming capacity of the latter. Polycarbonate blocks synthesized from macroinitiators such as PEG have been established by Hedricks et al, which have also found applications in the delivery of combination chemotherapy . Incorporation of wide varieties of tertiary amines as acid‐sensitive units in block copolymers has been used by Hammond et al to address delivery challenges in triple‐negative breast cancer .…”
Section: Introductionmentioning
confidence: 99%
“…To precisely control drug loading, one strategy to synthesize polymer-drug conjugates is to use hydrophobic drugs as initiators for the polymerization. 6066 Cheng and co-workers initially reported drug-initiated polymerization using a number of anticancer drugs such as paclitaxel and doxorubicin. 6163 …”
Section: Macromolecular Sapdsmentioning
confidence: 99%